2016
DOI: 10.2147/ndt.s120078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine on hippocampal neuron development and BDNF-TrkB signal expression in neonatal rats

Abstract: The study aimed to explore the effect of dexmedetomidine (DEX) on hippocampal neuron development process and on molecular expression of brain-derived neurotrophic factor (BDNF)-tyrosine receptor kinase B (TrkB) signaling pathway in neonatal rats. The hippocampal neuron cells were isolated from newborn neonatal rats and cultured in vitro. One control group and three treated groups with 1, 10, and 100 μmol/L DEX were used for the study. Cell activity and apoptosis were detected by the MTT and terminal deoxynucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In addition, Dex enhances the cholinergic anti-inflammatory pathway via α7nAChR ( Carr et al, 2018 ). The neuroprotective effect of Dex may be achieved by upregulating BDNF expression ( Lv et al, 2016 ).…”
Section: Advances In Treatmentmentioning
confidence: 99%
“…In addition, Dex enhances the cholinergic anti-inflammatory pathway via α7nAChR ( Carr et al, 2018 ). The neuroprotective effect of Dex may be achieved by upregulating BDNF expression ( Lv et al, 2016 ).…”
Section: Advances In Treatmentmentioning
confidence: 99%
“…Dexmedetomidine is widely used as an auxiliary drug in clinical anaesthesia. Previous study indicated that Dexmedetomidine could increase the BDNF expression in hippocampal neurons, implying that Dexmedetomidine may have a protective role in neurons. This was also confirmed by the finding that Dexmedetomidine increased acetylation level of histone in dopamine neurons, which was a molecular mechanism underlying the neuroprotective role of Dexmedetomidine .…”
Section: Introductionmentioning
confidence: 96%
“…Dexmedetomidine (Dex), which is an alpha-2 adrenergic receptor agonist drug, has been approved by the Food and Drug Administration (FDA) and is known for its anaesthetic, analgesic and neuroprotective effects ( 15 ). Dex also exerts a positive impact on neuronal development by regulating PSD95expression ( 16 ); however, the role of Dex in post-TBI neuroprotection remains unknown. The present study investigated the effect of Dex on the PSD95-NMDA interaction and subsequent functional recovery post-TBI.…”
Section: Introductionmentioning
confidence: 99%